Is there a mission drift in microfinance? Some new empirical evidence from Uganda - Francis Awuku Darko (University of Kent, School of Economics, 2016)
This paper considers the possibility of mission drift in microfinance; a situation where Microfinance Institutions (MFIs) move away from targeting the poor and towards better-off clients. Using two different measures of poverty, the paper examines whether microfinance institutions in Uganda follow a developmental objective by expanding their access to poorer districts; and if the pattern observed varies across different types of MFIs. The analysis is conducted on 118 MFIs over the period 2009-2013; adopting a static count data model and dynamic regression approach. We find that MFIs in Uganda are more likely to target richer districts during earlier years; however, poorer districts tend to catch up over time. This finding suggests that MFIs may wish to signal an improved financial performance by first establishing branches in better-off districts and then only later reaching out to poorer districts, employing cross-subsidisation. We also show that Commercial Bank MFIs are more likely to increase their presence in poorer districts than other types of MFIs, suggesting that protection against regulation and greater access to capital markets may make commercial MFIs the most qualified institutions to expand outreach to the unbanked segment of the world's poorer population.
Keywords: G21; I32; C25; 330; microfinance; poverty; mission drift; count data model